2007
DOI: 10.1055/s-2007-962836
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibilities of Bacteria Isolated from Ophthalmic Specimens between 1984 and 2005 in Zurich, Switzerland

Abstract: The data suggest that bacteria cultured from ophthalmic specimens in Zurich, Switzerland have not changed their pattern of antibiotic susceptibility over the past 20 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…This suggests that rate of antibiotic resistance in ocular P. aeruginosa is stable. Furthermore, reports of antibiotic resistance monitoring studies have shown that the antibiotic resistance pattern in eye isolates of P. aeruginosa has not substantially changed over this period . However, similar to the finding of this analysis, antibiotic resistance rate was higher in certain geographical locations .…”
Section: P Aeruginosa In Eye Infectionssupporting
confidence: 81%
“…This suggests that rate of antibiotic resistance in ocular P. aeruginosa is stable. Furthermore, reports of antibiotic resistance monitoring studies have shown that the antibiotic resistance pattern in eye isolates of P. aeruginosa has not substantially changed over this period . However, similar to the finding of this analysis, antibiotic resistance rate was higher in certain geographical locations .…”
Section: P Aeruginosa In Eye Infectionssupporting
confidence: 81%
“…Strain characterization is imperative because many isolates belonging to CoNS also reside as commensals in the extraocular tissues such as lids and conjunctiva. 1,8 Many techniques have been used to characterize strains of CoNS responsible for blood stream infections (BSI) and other device-related infections to determine the clonality, and also to conclusively distinguish clinically significant organisms from that of commensals or contaminants. 9 Such kind of comparative studies are lacking on CoNS isolates of ocular origin.…”
mentioning
confidence: 99%
“…17 A study by Maurer et al in Switzerland over 20 years on 7862 patients showed 38.3% positivity for aerobic bacteria. 18 19 This may be attributed to the small sample size and shorter duration of the study In present study, gram positive organism was most sensitive (100%) to vancomycin and chloramphenicol whereas gram negatives to moxifloxacin, tobramycin and gentamycin. Overall, ciprofloxacin was the most effective antimicrobial agents with susceptibility rate of 78.0%.…”
Section: Discussionmentioning
confidence: 61%